Analysis of Government Policy Implementation in Natural Disaster Management Through National Search And Rescue (Sar) In Indonesia - Kusworo Kusworo; Zubakhrum Tjenreng (Universitas Pancasakti Tegal, 2025)
Indonesia is highly vulnerable to natural disasters due to its geographical location at the convergence of three major tectonic plates. This study aims to analyze how the government implements policies to address disasters, particularly in the context of national-level Search and Rescue (SAR) operations. Using a qualitative descriptive method and a literature review approach, this research evaluates data from national policy documents, academic references, and Warfield’s (2008) disaster management theory. The findings reveal that although legal and institutional frameworks are in place through Law No. 24 of 2007 and the existence of BNPB and BASARNAS there are still major challenges in implementation. The main issues include weak inter-sectoral coordination, disparities in regional capacities, limited Search and Rescue (SAR) technology, and low levels of community preparedness. The integration of the six stages of disaster management proposed by Warfield (mitigation, preparedness, emergency response, recovery, capacity building, and adaptation) into Search and Rescue (SAR) policy has not been effectively implemented. There is a need to strengthen policies that are risk-based, sustainable, collaborative, and responsive to social and environmental changes. This study recommends improving inter-agency coordination, investing in Search and Rescue (SAR) technology, and empowering local communities as a strategic approach to disaster management in Indonesia. These findings highlight the need to strengthen inter-agency coordination and implement collaborative governance that can directly support the effectiveness of SAR policies at the practical level.